2019
DOI: 10.26460/md.v3i1.4284
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Insentif Terhadap Kinerja Karyawan Pada Pt Telesindoshop Kota Sorong

Abstract: This study knows wheter or not there is an effect of giving incentives to employee performance. Type of quantitative research with an associative approach. The research conducted in PT.Telesindoshop Sorong city. The sample us of 65 people. As for the data sources used are primary data and secondary data. Data analysis uses simple linear regression with Statistical Product and Service Solution (SPSS). Based on the results of this study indicate that the provision of PT.Telesindo’s incentives has an influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
2
0
0
4
Order By: Relevance
“…The results of the research that the author has done also support previous studies conducted by Meilawati (2019) which said that incentives had an influence on employee performance by 25.3%. Then Wiwin's research (2022) in his research revealed that giving incentives would have a positive and significant effect on employee performance of 26.6%.…”
Section: Effect Of Incentives On Employee Performancesupporting
confidence: 81%
“…The results of the research that the author has done also support previous studies conducted by Meilawati (2019) which said that incentives had an influence on employee performance by 25.3%. Then Wiwin's research (2022) in his research revealed that giving incentives would have a positive and significant effect on employee performance of 26.6%.…”
Section: Effect Of Incentives On Employee Performancesupporting
confidence: 81%
“…The results of the research that the author has done also support previous studies said that incentives had an influence on employee performance by 25.3% (Meilawati et al, 2019). Then other research revealed that giving incentives would have a positive and significant effect on employee performance of 26.6% (Soehardi et al, 2020).…”
Section: Effect Of Incentives On Employee Performancesupporting
confidence: 77%
“…Reliabilitas adalah ukuran suatu kestabilan dan konsistensi responden dalam menjawab hal yang berkaitan dengan konstruk-konstruk pertanyaan yang merupakan dimensi suatu variabel dan disusun dalam suatu bentuk kuesioner (Meilawati et al, 2019). Uji reliabilitas diukur dengan dua kriteria yaitu composite reliability dan cronbachs alpha dari blok indikator yang mengukur konstruk.…”
Section: B Uji Reliabilitasunclassified